Polygenic risk of Alzheimer disease is associated with early- and late-life processes. (2nd August 2016) - Mormino, Elizabeth C.; Sperling, Reisa A.; Holmes, Avram J.; Buckner, Randy L.; De Jager, Philip L.; Smoller, Jordan W.; Sabuncu, Mert R.
Abstract : Objective: To examine associations between aggregate genetic risk and Alzheimer disease (AD) markers in stages preceding the clinical symptoms of dementia using data from 2 large observational cohort studies. Methods: We computed polygenic risk scores (PGRS) using summary statistics from the International Genomics of Alzheimer's Project genome-wide association study of AD. Associations between PGRS and AD markers (cognitive decline, clinical progression, hippocampus volume, and β-amyloid) were assessed within older participants with dementia. Associations between PGRS and hippocampus volume were additionally examined within healthy younger participants (age 18–35 years). Results: Within participants without dementia, elevated PGRS was associated with worse memory ( p = 0.002) and smaller hippocampus ( p = 0.002) at baseline, as well as greater longitudinal cognitive decline (memory: p = 0.0005, executive function: p = 0.01) and clinical progression ( p < 0.00001). High PGRS was associated with AD-like levels of β-amyloid burden as measured with florbetapir PET ( p = 0.03) but did not reach statistical significance for CSF β-amyloid ( p = 0.11). Within the younger group, higher PGRS was associated with smaller hippocampus volume ( p = 0.05). This pattern was evident when examining a PGRS that included many loci below the genome-wide association study (GWAS)–level significance threshold (16, 123 single nucleotide polymorphisms), but not when PGRS was restricted to GWAS-level significant loci (18 single nucleotide polymorphisms). Conclusions: Effects related to common genetic risk loci distributed throughout the genome are detectable among individuals without dementia. The influence of this genetic risk may begin in early life and make an individual more susceptible to cognitive impairment in late life. Future refinement of polygenic risk scores may help identify individuals at risk for AD dementia.